Awareness about Biomedical Waste Management among Healthcare Professionals: Pharmaceutical Science-Biochemistry - Mahalakshmi, M.; Kalaiselvi, V.S.; Vasudevan, E.; Nivedhini, V.P. (International Journal of Life Science and Pharma Research, 2022)
Biomedical waste is the biggest challenge faced by healthcare sectors globally. The wastes are generated from all over the area of the hospital, and biomedical waste needs to be handled and discarded properly. The handling of biomedical waste (BMW) differs significantly from household or industrial trash. The collection and proper disposal of biomedical waste (BMW) has become a significant concern for the medical community. Effective Bio-Medical Waste management is both a legal and social responsibility. This study was undertaken to analyse hospital waste management knowledge and practices among healthcare providers in a tertiary care hospital and raise awareness about the management of biomedical waste from waste generation, handling, storage, proper treatment, and transport until the disposal of waste among the healthcare professionals. It was a questionnaire-based cross-sectional study conducted in Sree Balaji Medical College and Hospital from October 2020 to December 2020. The questionnaires were used to evaluate biomedical waste management knowledge, attitude, and practice (KAP) among doctors, laboratory technicians, non-technical staff, and undergraduate medical students. Pretest and post-test questions were designed. A questionnaire was used to conduct the pretest. A systematic teaching programme was developed following the pre-test, and a post-test was administered. It has been concluded that the health care professionals have a low level of Knowledge and awareness about biomedical waste management. The proper training, development, and implementation in biomedical waste management can improve healthcare sectors from polluting the environment and transmitting diseases. There should be regular, comprehensive BMW management training programmes for all employees, with tight implementation.